(untitled) (Transport systems and technologies, 2021)
The article considers the issues of analysis of the patterns of operation of the bearing elements of the bodies of carriage. The fleet of carriage mainly consists of models developed and manufactured in the 70-90s of the last century at car plants in Germany and Russia. They are obsolete both morally and physically. A comparative analysis of the size and nature of the operation of structural elements of both compartment cars and open cars. The results of the study made it possible to consider the issue of further use of carriage, which are most affected by corrosion. Key words: carriage, operation, rolling stock; corrosion, inventory, technical condition. The results of the study made it possible to consider the issue of further use of passenger cars, which are most affected by corrosion.